System‐specific evaluation of the dual flip angle MRI technique for quantitative T1 measurement. Issue 6 (20th April 2021) - Yee, Seonghwan; Fadell, Michael
Abstract : Purpose: To investigate if the accuracy of the dual flip angle (DFA) technique for T1 measurement is affected by the system‐specific RF excitation performance. Methods: A T1 phantom, made of 12 vials of unique T1 value ranging approximately from 200 ms to 2000 ms, was built and tested on seven different clinical scanners. For each experiment, the reference T1 of each vial was obtained by the inversion recovery‐based technique, and the DFA technique was applied repeatedly with several flip angle (FA) pairs conventionally proposed as optimal. The accuracy of the DFA technique for each FA pair was then evaluated by comparing the measured T1 values for the vials to the references. Any variation of the accuracy was then evaluated across different FA pairs, and across different MRI systems. To improve accuracy with a selected FA pair, the signal ratio (SR) curve, obtained from the phantom, was utilized in a calibration strategy of the DFA technique. Results: When combined for all the vials, the average ratio of the measured T1 to the reference generally increased as the FA pair window gradually slid from the smaller to the larger FA values. Furthermore, among several optimal FA pairs, the pair of the best accuracy varied slightly by the MRI system. The accuracy for any FA pair could be improved when the calibration strategy was utilized. Conclusions: The RF excitation performance may vary by the specific FA pair and by the specific MRI system, influencing the accuracy of the DFA technique. The system‐specific evaluation, and, if needed, its calibration, would help improve the accuracy of the DFA technique.